Effect of periconceptional folic acid supplementation on the risk of neural tube defects associated with a previous spontaneous abortion or maternal first-trimester fever. Issue 8 (15th July 2019) - Pei, Lijun; Wu, Jilei; Li, Jiajia; Mi, Xin; Zhang, Xiaofen; Li, Zhengyu; Zhang, Yuan
Abstract: STUDY QUESTION: Does maternal periconceptional no folic acid supplementation have an increased risk of neural tube defects (NTDs) associated with previous spontaneous abortion or first-trimester fever? SUMMARY ANSWER: Maternal periconceptional no folic acid supplementation can increase the risk of NTDs associated with previous spontaneous abortion or first-trimester fever, independent of known confounding factors. WHAT IS KNOWN ALREADY: Maternal periconceptional folic acid deficiency can increase the risk of NTDs. However, whether an interaction between periconceptional no folic acid supplementation and history of spontaneous abortion or first-trimester fever may have an increased risk of NTDs remains unknown. STUDY DESIGN, SIZE, DURATION: A population-based case–control study was performed including 104 nuclear families with offspring with NTDs and 100 control families with normal offspring between 1993 and 2002. PARTICIPANTS/MATERIALS, SETTING, METHODS: We investigated the potential interaction between periconceptional no folic acid use and a maternal history of spontaneous abortion or first-trimester fever in the risk for NTDs. Information on exposure factors was obtained at the onset of pregnancy, and pregnancy outcomes were collected during the first week after delivery or at the time of termination of the pregnancy. A multivariate logistic regression analysis was performed. MAIN RESULTS AND THE ROLE OF CHANCE: The interaction between periconceptional no folic acid use and a maternal history of spontaneous abortion markedly increased the risk of NTDs (adjusted odds ratio (aOR) 18.68, 95% CI, 4.43–78.76) after adjusting for potential confounding factors. The interaction coefficient was found to be 2.08, higher than 1, indicating that there is a significant interaction between two factors. Mothers who did not take periconceptional folic acid and had first-trimester fever had an increased risk of NTDs (aOR 21.81, 95% CI, 8.81–80.73). However, the interaction coefficient was found to be 0.62, less than 1, indicating that there is no significant interaction between two factors. LIMITATIONS, REASONS FOR CAUTION: A potential limitation was that the interval between the previous spontaneous abortion and the beginning of the subsequent pregnancy could not be estimated accurately, but was at least 1 year or more. WIDER IMPLICATIONS OF THE FINDINGS: We emphasize that a previous spontaneous abortion may represent a first occurrence of NTDs rather than be the cause of NTDs. Our findings indicate that mothers with a history of spontaneous abortion are ideal candidates for periconceptional folic acid supplementation. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by National Natural Science Foundation of China (41871360) and Danone Nutrition Center for Dietary Nutrition Research and Education Foundation (DIC2015-05). There are no competing interests to declare.